Islamic Educational Values in the Mambubur Asura Tradition in Landasan Ulin Tengah Sub-District, RT 01, Banjarbaru City - Wandaristy Zahratul Imani; Najminnur Hasanatun Nida (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Indonesia has a diverse cultural wealth, including Islamic traditions that are acculturated with local wisdom. This study examines the values of Islamic education in the mambubur asura tradition in Landasan Ulin Tengah Village, RT 01, Banjarbaru City, which is held every 10 Muharram. Qualitative research methods with a field approach were used to understand the meaning behind this tradition. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that this tradition contains educational values of faith, sharia, and morals, such as strengthening faith, praying together, mutual cooperation, and giving alms. Implementation factors include the purpose of commemorating 10 Muharram, the motivation of the Muslim community, and the existence of supporting facilities. This tradition also serves as a medium for learning Islamic values and strengthening community ties. Although the pandemic had stopped this tradition in 2021, it was implemented again in 2022 with the spirit of maintaining local Islamic culture.